2016
DOI: 10.1021/acs.jpcc.6b07939
|View full text |Cite
|
Sign up to set email alerts
|

Water Interactions with Nanoporous Silica: Comparison of ReaxFF and ab Initio based Molecular Dynamics Simulations

Abstract: Detailed understanding of the reactions and processes which govern silicate–water interactions is critical to geological, materials, and environmental sciences. Interactions between water and nanoporous silica were studied using classical molecular dynamics with a Reactive Force Field (ReaxFF), and the results were compared with density functional theory (DFT) based ab initio molecular dynamics (AIMD) simulations. Two versions of ReaxFF Si/O/H parametrizations (Yeon et al. J. Phys. Chem. C2016120305 and Fogart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 90 publications
8
107
0
Order By: Relevance
“…59 Rimsza et al used DFT-based ab initio MD simulations of waternanoporous silica interactions to validate two versions of ReaxFF potentials for water-silica interactions. 60 It was shown that the new refined model (ReaxFF-2015) can describe the reaction energy barrier of Si-O-Si breakage (hydrolysis reaction) much better than the 2010 version (Fig. 8a).…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 97%
“…59 Rimsza et al used DFT-based ab initio MD simulations of waternanoporous silica interactions to validate two versions of ReaxFF potentials for water-silica interactions. 60 It was shown that the new refined model (ReaxFF-2015) can describe the reaction energy barrier of Si-O-Si breakage (hydrolysis reaction) much better than the 2010 version (Fig. 8a).…”
Section: First-principles-based Simulations Of Glass-water Interactionsmentioning
confidence: 97%
“…For example, within glass corrosion, classical and ab initio molecular dynamics (MD) simulations are prominently used to generate realistic bulk and surface structures of waste glasses, [215][216][217][218] including the nanoporous gel layer structures during glass corrosion. 219,220 To a lesser degree, MD has also been used to describe ceramics and metal corrosion and inhibition. 221 MD has not been more widely used because of the limited availability of interatomic potentials to describe the heterogeneous interfaces.…”
Section: Silicate Glass Crystalline Ceramic and Metal Corrosion: Simentioning
confidence: 99%
“…use of a reactive potential is critical for analyzing all the reactions and material transport inside the glass and solution. Recent improvements of reactive MD force fields have allowed for several advances in the modeling of silica‐water interactions . In one of the most recent studies of sodium silicate hydration with the ReaxFF, leaching of sodium into water and accumulation at the interface of the leached Na + ions was observed along with proton transport inside the glass in the first nanosecond of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements of reactive MD force fields have allowed for several advances in the modeling of silica-water interactions. [33][34][35][36][37][38] In one of the most recent studies of sodium silicate hydration with the ReaxFF, 39 leaching of sodium into water and accumulation at the interface of the leached Na + ions was observed along with proton transport inside the glass in the first nanosecond of reaction. Another recent study with the same ReaxFF potential studied the continuation of these simulations for a longer time (3 ns) and for different temperatures.…”
mentioning
confidence: 99%